Oophorectomy or ovarian conservation at the time of hysterectomy for benign disease. (22nd April 2022) - Asfour, Victoria; Jakes, Adam D; McMicking, Jess; Szetho, Wei Zian; Sayasneh, Ahmad; Diab, Yasser; Mascarenhas, Lawrence; Rymer, Janice
Abstract : Key content: Bilateral salpingo‐oophorectomy is indicated for patients with suspected or confirmed gynaecological malignancy. Risk reduction surgery is indicated in patients with a significant family history or a genetic predisposition to developing breast or ovarian cancer. Bilateral salpingectomy with ovarian conservation reduces the risk of ovarian cancer, whilst preserving ovarian function. Oophorectomy prior to the menopause is associated with increased all‐cause mortality and significant menopause related morbidity. Conservative measures such as weight loss, family planning and lifestyle advice could reduce the overall lifetime risk of ovarian cancer. Learning objectives: To understand the rationale of the decision‐making process for bilateral salpingo‐oophorectomy or bilateral salpingectomy with ovarian conversation at the time of hysterectomy for benign disease. To understand the risk–benefit balance of performing oophorectomy in the context of risk reduction of high‐risk patients compared with patients with no genetic predisposition or family history. To consider conservative risk reduction measures that do not involve oophorectomy. Ethical issues: In the absence of family history or genetic predisposition to ovarian or breast cancer, is it ethical to perform routine oophorectomy in perimenopausal or even postmenopausal women? Is it ethical to reduce the risk of ovarian cancer while increasing all‐cause mortality and menopause‐related morbidity? Is it ethical to offer bilateral salpingectomy as a female sterilisation procedure?